2018
DOI: 10.1055/s-0036-1591962
|View full text |Cite
|
Sign up to set email alerts
|

A New Simple Procedure for the Synthesis of Heptamethyl Cyclohepta-1,3,5-triene-1,2,3,4,5,6,7-heptacarboxylate

Abstract: A new and simple procedure for the synthesis of heptamethyl cyclohepta-1,3,5-triene-1,2,3,4,5,6,7-heptacarboxylate in a 51% yield is presented. An optimization of the reaction conditions was performed, and a convenient protocol for the isolation of the reaction product was developed. The structure of the key electrophilic intermediate was determined by means of NMR spectroscopy, and a plausible reaction mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Our previous investigations of polyunsaturated cyclic molecules abundant with electron‐withdrawing groups revealed their rich reactivity towards either nucleophilic or electrophilic reagents as well as in the pericyclic reactions . One of the key synthons therein was 1,2,3,4,5,6,7‐hepta(methoxycarbonyl)cycloheptatriene (HMCH),, as well as its closely related carbocyclic analogs, relatively high acidity of HMCH being one of the key properties determining its high reactivity . Electron‐deficient 1,2‐diazepines are analogues of HMCH in which the two C–CO 2 Me moieties are substituted with nitrogen atoms which similarly stabilize the negative charge.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous investigations of polyunsaturated cyclic molecules abundant with electron‐withdrawing groups revealed their rich reactivity towards either nucleophilic or electrophilic reagents as well as in the pericyclic reactions . One of the key synthons therein was 1,2,3,4,5,6,7‐hepta(methoxycarbonyl)cycloheptatriene (HMCH),, as well as its closely related carbocyclic analogs, relatively high acidity of HMCH being one of the key properties determining its high reactivity . Electron‐deficient 1,2‐diazepines are analogues of HMCH in which the two C–CO 2 Me moieties are substituted with nitrogen atoms which similarly stabilize the negative charge.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Moreover, we found that the reaction does not occur in the presence of other bases apart from pyridine (triethylamine, potassium acetate). Furthermore, we have recently shown [15] that hepta(methoxycarbonyl)cycloheptatriene 4 (HMCH) is formed in the reaction of N-(methoxycarbonylmethyl)pyridinium and either dimethyl dibromosuccinate 5 or bromomaleate 6 in the presence of pyridine. [15] Therein we provided the evidence that the key electrophilic intermediate in the formation of 4 is the di(methoxycarbonyl)vinylpyridinium ion 7.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have recently shown [15] that hepta(methoxycarbonyl)cycloheptatriene 4 (HMCH) is formed in the reaction of N-(methoxycarbonylmethyl)pyridinium and either dimethyl dibromosuccinate 5 or bromomaleate 6 in the presence of pyridine. [15] Therein we provided the evidence that the key electrophilic intermediate in the formation of 4 is the di(methoxycarbonyl)vinylpyridinium ion 7. So, here we propose that the formation of cycloheptadienes 3a,b is similar to that of HMCH and includes intermediate 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above experimental observations and previous reports, , a plausible reaction mechanism for the synthesis of indolizines was proposed in Scheme . First, in the presence of Cs 2 CO 3 , the pyridinium salt would be deprotonated to afford ylide A which could capture the difluorocarbene to afford B .…”
mentioning
confidence: 99%